PENINGKATAN PROFESIONALISME GURU BAHASA INDONESIA - Hamsa, Akmal (Diksi, 2009)
Changes in the educational system in Indonesia aim to meet the demands of theera, including the science and technology, economic, social, political advancements andsociety's structure. Education functions as an accelerator for such advancements so that itrequires ideal programs. Subject matter teachers are expected to be able to understand andimplement such programs in order to attain the advancements. However, in practice, thereare a lot of constraints. Some constraints concern the human resources and this results ineducation of low quality. Such constraints can be overcome through a policy and strategyfocusing on decentralization and autonomy in education. It is necessary to improve teacherprofessionalism by eliminating obstacles through teacher trainings to get rid of personal,economic, structural, social, and cultural constraints. To do so, it needs the government'spolitical will, teacher commitment, and society involvement.Keywords: improvement, professionalism